The Journey from Kyc to Aadhaar Based E-Kyc Service: the Much Needed Change Impetus For Financial Inclusion: Exploring the Evolution and Impact of E-KYC in India's Financial Landscape (Journal of Advances and Scholarly Researches in Allied Education, 2015)
A risky and compliance environmentis becoming increasingly important in financial institutions, and a bank'scustomer is a critical component of this increasingly regulated and monitoredenvironment. Financial institutions are constantly working to identify andprevent the customers who are perpetrating financial crimes and non-compliantactivities and are using the financial institution to meet their illegal goals.Without this due diligence, banks can become subject to reputational,operational, legal and compliance risks, which can result in significantfinancial cost. This is where the Know Your Customer (KYC) norms come intopicture, which enables the banks to know/understand their customers and theirfinancial dealings to be able to serve them better. It calls for immenseattention on the part of regulatory authorities for creating a sustainable KYCmechanism as India makes efforts for progressing on the path of financialinclusion, inclusive growth coupled with a commitment for an effectiveanti-money laundering regime. The present paper attempts to study the KYCmechanism in the Indian context, including its background and its importance asan indispensable part of an effective anti-money laundering (AML) regime. Thisstudy will also shed light on the issues, problems, challenges and varioustypes of risks being faced while implementing KYC norms. Morever ,the recentwaves of mal-practices and incidences of lapses in observing Know your customer(KYC) norms and Anti Money Laundering (AML) standards in the Indian BankingSystem has once again put forth the issue to a considerable public domain,which makes it imperative to re-visit the present KYC norms and look for futurechallenges and opportunities that lies ahead. In this context, the presentstudy also attempts to study the evolution of e-KYC in India and its importanceas a game changer for financial inclusion till now.